(Un)anticipated Monetary policy in a DSGE model with a shadow banking system (Bank of Finland Research Discussion Paper 4/2013) - Fabio Verona (2013)
Motivated by the U.S. events of the 2000s, we address whether a too low for too long interest rate policy may generate a boom-bust cycle. We simulate anticipated and unanticipated monetary policies in state-of-the-art DSGE models and in a model with bond financing via a shadow banking system, in which the bond spread is calibrated for normal and optimistic times. Our results suggest that the U.S. boom-bust was caused by the combination of (i) interest rates that were too low for too long, (ii) excessive optimism and (iii) a failure of agents to anticipate the extent of the abnormally favourable conditions.